Prevention of Local Anesthetic Systemic Toxicity. Issue 2 (1st February 2010) - Mulroy, Michael F.; Hejtmanek, Michael R.
Abstract : Although new drugs and techniques may improve outcomes when unintended high blood levels of local anesthetics occur, the primary focus of daily practice should remain the prevention of such events. Although adoption of no single "safety step" will reliably prevent systemic toxicity, the combination of several procedures seems to have reduced the frequency of systemic toxicity since 1981. These include the use of minimum effective doses, careful aspiration, and incremental injection, coupled with the use of intravascular markers when large doses are used. Epinephrine remains the most widely used and studied marker, but its reliability is impaired in the face of β-blockade, anesthesia, advanced age, and active labor. As an alternative, the use of subtoxic doses of local anesthetics themselves can produce subjective symptoms in unpremedicated patients. Fentanyl has also been confirmed to produce sedation in pregnant women when used as an alternative. The use of ultrasound observation of needle placement and injection may be useful, but has also been reported as not completely reliable. Constant vigilance and suspicion are still needed along with a combination of as many of these safety steps as practical.